REPRESENTASI FRAME DALAM LATAR BELAKANG WACANA TAJUK TENTANG TERORISME - Subagyo, P Ari (LITERA, 2016)
This study aims to describe the representations of frames in the backgrounds of editorials on terrorism. It uses the critical pragmatic approach combining pragmatics and critical discourse analysis (CDA). There are three frames in the editorials on terrorism in four national dailies in Indonesia (Suara Pembaruan, Republika, Kompas, and Koran Tempo) in accordance with their ideologies (historical backgrounds and affiliations). The study proves that the three frames are systematically represented in the backgrounds of editorials on terrorism. Suara Pembaruan, Republika, Kompas, and Koran Tempo represent their frames in their own ways. Each daily uses the background to present information or opinions according to its frame.